The home bias in sovereign ratings: conference paper - Fuchs, Andreas; Gehring, Kai (Jahrestagung des Vereins für Socialpolitik 2014, 2013)
Credit rating agencies are frequently criticized for producing sovereign ratings that do not accurately reflect the economic and political fundamentals of rated countries. This article discusses how the home country of rating agencies could affect rating decisions as a result of political economy influences and culture. Using data from nine agencies based in six countries, we investigate empirically if there is systematic evidence for a home bias in sovereign ratings. Specifically, we use dyadic panel data to test whether, all else being equal, agencies assign better ratings to their home countries, as well as to countries economically, politically and culturally aligned with them. While most of the variation in ratings is explained by the fundamentals of rated countries, our results provide empirical support for the existence of a home bias in sovereign ratings. We find that the bias becomes more accentuated following the onset of the Global Financial Crisis and appears to be driven by economic and cultural ties, not geopolitics.